THE EFFECT OF USING SERIES IMAGE MEDIA ON NARRATIVE WRITING SKILLS (International Conference on Social and Islamic Studies, 2022)
The purpose of this study: (1) To describe the improvement of students' narrative essay writing skills before using serial picture media (2) describes the improvement of students' essay writing skills after applying serial picture media iMattoanging, (3) analyzes that there is an effect of applying serial picture media to the narrative essay writing skills of students of class . This research is a comparative quantitative research with the approach of Pre-Experimental Design with the type of One-Group Pretest-Posttest design. Sampling was carried out using saturated sampling technique, namely 21 students. The research instruments used were performance tests, observations, and documentation. The data analysis technique used is descriptive statistical analysis and inferential statistics by conducting a T test. The results of the study through IMB SPSS Statistics Version 24 showed that students' narrative essay writing skills before using pretest serial media images obtained an average of 48 in the less category. . The results of students' narrative essay writing skills after using the posttest serial image media obtained an average of 88 in the very good category. The effect of using serial picture media on students' narrative essay writing skills can be seen from the hypothesis test which shows t count = 10.087> t table = 1.72 with a real level = 0.05 so that t count is in the H0 resistance area, which means H0 was rejected and the HI hypothesis was accepted. The implication of the research is that superior teachers know and understand the principles of learning and mastering the skill of writing narrative components as a guide for managing a good class.